(untitled) (Andamios, Revista de Investigación Social, 2016)
There are different models to conceive rural extension. In order to describe the conceptions of rural extension supported by rural extensionists working in ten different Latin American countries, a survey was conducted. The sample was non-probabilistic, incidental (n=589). The conception of rural extension of the surveyed extensionists is mainly supported in the transfer of technology model, with important differences among the different samples. The Uruguayan sample features a dialogical model. In no sample appeared ideas related to local/territorial development or to innovation systems approach. Actions towards consciously and critically choosing the extension model to be implemented are recommended.